PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP KETERAMPILAN BERBICARA MAHASISWA PBSI UNIVERSITAS MUHAMMADIYAH JEMBER - Ayunda Putri Nazarrina; Neyskia Ramadila; Marisa Nur Rohma; Annisa Dallilatul Hasanah; Agus Milu Susetyo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the effect of social media usage intensity on the speaking skills of students in the Indonesian Language and Literature Education (PBSI) Study Program at the University of Muhammadiyah Jember. Using a quantitative approach with a causal correlational design, the study involved 150 students selected through a purposive sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression using SPSS version 25. The results showed that social media usage intensity had a significant negative effect on speaking skills (Y = 87.342 - 0.456X; p < 0.05) with a coefficient of determination of 48.7%. The higher the intensity of social media usage, the lower the students' speaking skills. This finding indicates that excessive social media use reduces opportunities for direct verbal communication practice, thus necessitating learning strategies that positively integrate social media to develop the communication skills of prospective Indonesian language teachers.